Κατάθεση ΄73 - Αναγνωστάκης, Μανόλης Α., 1925-2005 (Μπουκουμάνης, 1973)
Γιώργος Σεφέρης , Γιάννης Ρίτσος , Μανόλης Άναγνωστάκης , Νάνος Βαλαωρίτης , Τάκης Σινόπουλος Θ. Δ. Φραγκόπουλος , Χρήστος Ν. Βαλα6ανίδης , Άνέστης Εύαγγέλ0Ι.) , Όλυμπία Καράγιωργα , Λευτέρης Κανέλλης , Γιάννης Κοντός , Μένης Κουμανταρέας , - Ερση Λάγκε , Μαρία Λαϊνά , Άνδρέας Λεντάκης , Γιάννης Μαντζουράνης , Κώστας Μαυρουδής , Λία Μεγάλου , Ροδόλφος Μορώνης , Νίκος Μοσχοβάκος , Σοφία Μοσχόβη , Στέφανος Κ. Μπεκατώρος , Δημήτρης Μυταράς , Θανάσης Θ. Νιάρχος , Κώστας Γ. Παπαγεωργίου , Σάκης Παπαδημητρίου , Θανάσης Χ. Παπαδόπουλος , Βλάσης Παπασπύρου , Κατερίνα Πλασσαρά , Δημήτρης Ποταμίτης , Λεφτέρης Πούλιος , Ντίνος Σιώτης , Γιώργος Ε. Στεφανάκης , Ελενα Στριγγάρη , Βαγγέλης Χατζηδημητρίου , Νατάσα Χατζιδάκη , Andrci Codrescou , Paul Mariah , Ρομπέρ Ι. Ροζντεστβένσκι , Χαρακτικό Βάσω Κατράκη